Odpowiedź :
[tex]a) \ -4 + \frac{2}{9} = -\frac{36}{9} + \frac{2}{9} = \frac{34}{9} = 3\frac{7}{9}[/tex]
[tex]b) \ 8 - 9,2 = -1,2[/tex]
[tex]c) \ -2+(-1,5) = -2 - 1,5 = -3,5[/tex]
[tex]d) \ -3-(-1\frac{2}{3}) = -3 + 1\frac{2}{3} = -\frac{9}{3} + \frac{5}{3} = -\frac{4}{3} = -1\frac{1}{3}[/tex]
Mam nadzieję, że pomogłam ;)
Pozdrawiam
Odpowiedź:
a). -4 + 2/9 = -34/9 = -3 7/9 lub 3,7
b). 8 - 9,2 = -1,2 lub - 1 1/5
c). -2 + (-1,5) = -3,5 lub -3 1/2 lub - 7/2
d). - 3 - (- 1 2/3) = - 3 - 4/3 = 1 1/3
Szczegółowe wyjaśnienie: